Consider the following function values http://oi61.tinypic.com/msoiuc.jpg also given http://oi57.tinypic.com/2cxux5h.jpg a ) Set up a system of equations...
Consider the following function values http://oi61.tinypic.com/msoiuc.jpg also given http://oi57.tinypic.com/2cxux5h.jpg a ) Set up a system of equations...
g(x) = 3x-2 f(x)= 4x-1 find g(-7) - f(-7)
a) y=x3 + e2x b) y=5xe-4x c) y=x2e-(x^x)
1. f(x)= |x|; g(x)= |x-3| a.) f+g b.) f-g c.) f⋅g d.) f/g e.) g/f 2. f(x)=1/(x+1); g(x)=x/(x-2) a.) f+g b.) f-g c.) f⋅g d.)...
I. Solve each item completely. 1. Shipping charges are often based on a formula that offers a lower charge per pound as the size of the shipment is increased. Suppose shipping charges...
if f(x)=log(1+x)/(1-x) g(x)=(3x+x2)/(3x2+1) prove that(f°g)(x)=3f(x)
f(x)=sin^4x+cos^4x
I'm completely lost on the below question. Can someone please show me how this is done. Analytically show that the function f(x)=x^3+5x+6 is one-to-one. Use Theorem 5.2 to help...
f(x)={x} {x}=x-[x] Find the periodicity of the functions : f(x)={ax} and f(x)=a{x}
a) f(x)=sinx+cosx b) f(x)=sin4x+cos4x especially this one! c) f(x)= ln(cosx) d) f(x)=sin4x+sin6x
Consider the functions f(x)= (x*x)-1/x+1 and g(x)=x-1.
Consider the functions f(x)= (x*x)-1/x+1 and g(x)= x-1
For f(x)=4x^3, construct and simplify the difference quotient f(x+h)-f(x)/h Just so there is no confusion f(x+h)-f(x)/h means...
The expression f(x+h)-f(x)/h for h ≠0 is called the difference quotient. Find and simplify the difference quotient for the following function. f(x)= -3x^2+9x+4 f(x+h)-f(x)/h...
g(x)=(x-3)/11 h={(-3,-8),(3,9),(4,-3),(9,0)} a. g^-1(x)= b.(gog^-1)(0)= h^-1(9)=
If h(t)=4t2+3t-1 and v(t)=3t+2, calculate h(v-1(t))
Find the domain of the following functions. a.) p(t)=1/t2-4 b.) t(a)=4√a-2
Let f(x)=(2x+1)/(x+1). For what value of x is f(x)=0.3?
The number of milligrams of a drug that remains in a patient's system after t hours is given by the function A(t) = Iert. Ted was given 200 milligrams of medicine which leaves his bloodstream at a...
1) x-axis and f(x)=2x-x^2 2) f(x)=x^2 and g(x)=x 3) f(x)=x^3-3x and g(x)=x